Assessment of Airborne Particles Generated During Cattle Processing - Maduforoh, Collins; Horsfall, Esther Omoni (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
This paper investigates the environmental implications of pollution stemming from cattle processing facilities in Port Harcourt, Nigeria, focusing on air quality degradation due to suspended particulate matter (SPM). Utilizing a fully randomized block design, data on SPM2.5 and SPM10 concentrations were collected over a twelve-month period from five slaughterhouse locations. The findings revealed consistently elevated levels of SPM across all sites, exceeding the recommended standards set by the World Health Organization. Analysis indicated that industrial activities associated with cattle processing, such as combustion processes and waste disposal, significantly contribute to air pollution in the study area. The implications of high SPM levels extend beyond immediate health risks to include broader environmental concerns, particularly regarding climate change and biodiversity loss. This study underscores the urgent need for intervention measures to mitigate the adverse impacts of pollution from cattle processing on both human health and the environment. Recommendations include implementing stricter regulatory measures, investing in research and development of cleaner technologies, providing incentives for sustainable practices, and fostering collaboration among stakeholders. Addressing these challenges requires a multifaceted approach and concerted efforts from government agencies, non-governmental organizations, academia, and the private sector. By prioritizing environmental stewardship and adopting sustainable practices, we can work towards a healthier, more resilient future for communities affected by pollution from cattle processing.